Pengaruh Proporsi Silica Fume Dengan Penambahan Zat Additive Terhadap Kuat Tekan Mortar - Novita, Ayik Asri; Pranowo, Dadang Dwi; Amin, M. Shofi’ul; Utanaka, Ahmad; Santoso, Catur Bejo (Indonesian Society of Applied Science, 2025)
Mortar is commonly used in construction as a strong and durable building mixture that is relatively easy to make. One of the problems that often occurs in Indonesia, especially in buildings located in coastal areas, is the rapid rusting of reinforcement or the degradation of bricks due to not receiving sufficient protection from mortar as the outermost part. Mortar plays a crucial role in construction by acting as an adhesive for bricks, wall plaster, and ceramic tiles, while also providing protection for construction joints. Because of this, the mortar needs to have the maximum strength possible. Adding alternative ingredients, such as silica fume and Superplasticizerconsol SS 74 N, to the mortar is one way to achieve this goal. Different amounts of 0.5% Superplasticizer and 10% and 20% silica fume percentage were added, and compressive strength tests were conducted after 7, 14, and 28 days. The results of the research show that the effect of adding Silica fume and Superplasticizer to mortar has the potential to reduce the compressive strength value, with the maximum compressive strength value for normal mortar aged 28 days being 49.41 Mpa, while for mortar variations of SF 10% and 20% 37.48 Mpa and 30.43 Mpa.